Estudio de la incidencia de la velocidad de impacto de material particulado en acero AISI 1020 - Pacheco Barragán, Hernan Camilo (Escuela Colombiana de Ingeniería Julio Garavito, 2021)
Colombia has an extended territory where some regions are far away from urban centers. The electrical connections in those areas are very scarce because the geographical conditions. Therefore, different initiatives are proposed to develop electrical solutions, such as: vertical axis wind turbines (VAWT). These devices require little space for installation, low costs and low wind speed regimes. VAWT are exposed to several environmental conditions which lead to degradation phenomena such as erosion and corrosion-erosion. The main factors that interfere and promote these phenomena are wind speed, impact speed, size, type and composition of particulate material, impact angle and salinity of the environment. This work identifies the behavior of a steel AISI 1020, which is commonly used in structures and devices exposed to the environment. In this study, experimental conditions similar to those of the Colombian Guajira were simulated. The variation of these conditions approaches the system to the phenomenon and check the results reported in literature. The impact angles of particles close to 30° increase the effect of surface deterioration and material loss , since under this inclination the surface decreases its capacity to absorb energy of the impact, which leads to higher material removal. In conclusion, the design of devices such as wind turbines (axes, blades) or structures exposed to aggressive environments should avoid designs where materials are under angles closer to 30° even more, where the regimes are around a speed wind rate of 15 m/s, because material loss under this conditions will be significant.
Keywords: Turbinas eólicas; Erosión; Ángulo de impacto; Velocidad de Impacto; Partículas sólidas; Desgaste; Corrosión-erosión; Wind turbines; Erosion; Impact angle; Impact speed; Silod particles; Wear; Corrosion-erosion